SUPERVISI DALAM AL-QUR’AN DAN HADITS - Kusyaeni (Department of Islamic Education Management, 2023)
The purpose of this research is to explore, analyze and describe the concept of supervision contained in the Al-Qur’anand Hadith. This research is a library research.The primary data used in the secondary data is derived from the verses of the Quran and Hadith. While the secondary data are books, journals, and article related to supervision. In this study, researcher used the maudhu’i interpretation method approach (thematic) in identifying and describing how supervision is the Quran and Hadith. The result of the study show that the verses related to the term supervision are contained in four words, namely: 1) Al-khabir QS. Al-An’am: 18, QS. Al-Mulk: 14, dan Al-Isra’: 96), term asy-syahid (QS. Al-baqarah: 140, QS. Al-Baqaarah: 204, QS. Ali-Imrarn: 81, QS. Ali-Imran: 98, QS. Ali-Imran: 99, dan QS. An-Nisa: 33), term ‘Alima (QS. Al-Mujadalah: 7, QS. Al-Baqarah: 77, dan QS. An-Nahl: 23), 4) term Harasa (QS. Al-Jinn: 8). While the hadiths related to the term supervision contained in the hadith are as follows: 1) hadith of jibril about ihsan, hadith about the order of Rasulullah Saw to vomit alms dates which were eaten by his grandson sayyidina Hasan r.a, hadith about the order of Prophet Saw to complete ablution by washing heel perfectly, hadith about the Prophet’s order to repeat his prayer because it was not tumakminah, hadith the Prophet reprimanded immediately, hadith abaout exlainiing mistakes from the Shari’a point of view, hadith about not rushing to blame other people’s mistakes, hadith about wranign gently and hadith about practise what is advised.